Response Surface Methodology On Wax Deposit Optimization - Norida, Ridzuan; Zulkefli, Yaacob; Fatmawati, Adam (Universiti Kebangsaan Malaysia, 2017)
In this study, the application of response surface method design based on rotatable central composite design (CCD) was used to optimize wax deposit using Design Expert 7.1.6 software. The process consisted of 13 experiments involving eight factorial points and five replications at the center point. The influence of operating parameters on the weight of wax deposit was investigated using cold finger apparatus. The experimental result indicated that the amount of wax deposit was significant due to factors of cold finger temperature and experimental duration. The wax deposit amount decreased significantly with the decrease of experimental duration when the cold finger temperature increased to 25 °C. The minimum value of 0.0042 g of wax deposit was obtained at the optimized conditions of 1.5 hours and 25 °C, respectively.